The Role of Fake News in Shaping Public Perception and Trust in the Media - Deepak Kem (Journal of Social Science Utilizing Technology, 2024)
Social media platforms, which include emotionally charged bits of information, are susceptible to the widespread spread of large quantities of false information. There is less knowledge about the emotional processing that drives people's beliefs and the spreading of false news on social media. Most of the studies on fake news have mostly focused on cognitive processing characteristics. This research conducts a comprehensive analysis of how emotional factors influence the way people perceive false information on social media sites. A thorough literature search was performed in the SCOPUS and Web of Science databases to locate pertinent publications on the subjects of effect, misinformation, disinformation, and false news. A total of 31 empirical publications were acquired and scrutinized. This review identified seven research topics and four research gaps. This review's results enhance the current body of work on the cognitive processes involved in individuals' perception of false information on social media. These ramifications may affect technological platforms, governments, and people who are engaged in fighting against infodemics.